Diets within Environmental Limits: The Climate Impact of Current and Recommended Australian Diets - Ridoutt, Bradley (Nutrients, 2021)
Planetary boundaries are an important sustainability concept, defining absolute limits for resource use and emissions that need to be respected to avoid major and potentially irreversible earth system change. To remain within the safe operating space for humanity, there is a need for urgent adoption of climate-neutral diets, which make no additional contribution to warming. In the first study of its kind, a new climate metric, the Global Warming Potential Star (GWP*), was used to assess greenhouse gas (GHG) emissions associated with 9341 Australian adult diets obtained from the Australian Health Survey. Dietary climate footprints averaged 3.4 kg CO(2)-equivelent per person per day, with total energy intake explaining around one quarter of the variation. Energy-dense and nutrient-poor discretionary foods contributed around one third. With lower climate footprint food choices, a diet consistent with current Australian dietary guidelines had a 42% lower climate footprint. Currently, it is not possible to define a climate-neutral dietary strategy in Australia because there are very few climate-neutral foods in the Australian food system. To bring Australian diets into line with the climate stabilization goals of the Paris Agreement, the most important need is for innovation across the agricultural and food processing industries to expand the range of climate-neutral foods available.